2002
DOI: 10.1145/964725.633048
|View full text |Cite
|
Sign up to set email alerts
|

Route oscillations in I-BGP with route reflection

Abstract: We study the route oscillation problem [16, 19] in the Internal Border Gateway Protocol (I-BGP)[18] when route reflection is used. We propose a formal model of I-BGP and use it to show that even deciding whether an I-BGP configuration with route reflection can converge is an NP-Complete problem. We then propose a modification to I-BGP and show that route reflection cannot cause the modified protocol to diverge. Moreover, we show that the modified protocol converges to the same stable routing configuration rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 10 publications
0
59
0
Order By: Relevance
“…Applying Addpath, routers may provide their internal peers with clearly more information than common iBGP allows. The ability to advertise several paths per prefix in parallel led to the development of several path diversity schemes [14][15][16][17]: schemes, that would cause a significant load growth. Analyses for the Route Server architecture showed that scalability can be evaluated efficiently [16].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Applying Addpath, routers may provide their internal peers with clearly more information than common iBGP allows. The ability to advertise several paths per prefix in parallel led to the development of several path diversity schemes [14][15][16][17]: schemes, that would cause a significant load growth. Analyses for the Route Server architecture showed that scalability can be evaluated efficiently [16].…”
Section: Related Workmentioning
confidence: 99%
“…These schemes are specified in separate working documents [14,15] and iBGP architecture proposals, cf. [16] or [17], for example.…”
Section: The Add-path Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, our algorithm will on average use fewer messages and less memory to prevent oscillations than the one presented in [1].…”
Section: Introduction the Internet Consists Of Millions Of Routersmentioning
confidence: 97%
“…al. [1]. Their solution solves the problem by letting route reflectors retransmit all routes, not only the best route.…”
Section: Introduction the Internet Consists Of Millions Of Routersmentioning
confidence: 99%